Prior Complaint Evidence under the Evidence Act 2006: The Supreme Court Jurisprudence - Hill, Holly (Victoria University of Wellington Law Review, 2012)
At the time of writing, the Evidence Act 2006 has been in force for almost five years, but in several respects it has failed to fulfil its mandate of clarifying and simplifying New Zealand’s rules of evidence. One area where this failure can be seen as most evident is in respect of evidence of prior complaints of sexual offending. Here, the rule governing previous consistent statements in s 35(2) of the Act radically changes the previous common law position, enacting entirely unfamiliar technical requirements in its place. This article provides thorough analysis of the problems with s 35(2) through an analysis of cases where the Supreme Court has struggled to interpret and apply the provision. Ultimately the article suggests that a less technical reform will provide the necessary simplicity and certainty that is currently absent from the provision.